SISTEM MONITORING LAMPU JARAK JAUH BERBASIS WIFI DAN BLYNK MENGGUNAKAN ESP32 PADA LINGKUNGAN SIMULASI WOKWI - Akhlis Munazilin; Siti Akila Nisrina; Shofiyana Herman; Ummariatul Fitriyah (CV. Denasya Smart Publisher, 2026)
Internet of Things (IoT)-based lighting control systems enable users to monitor and control electronic devices remotely via internet connection. This study aims to develop and implement a WiFi-based lighting monitoring and control system using an ESP32 microcontroller integrated with the Blynk platform. System development and testing were carried out in the Wokwi simulation environment. The research employed a prototype method with an experimental approach. This approach consisted of requirements analysis, system design, implementation, integration with Blynk Cloud, and system testing. In the developed system, ESP32 functions as the main controller, a relay acts as the actuator, and an LED represents the lamp. Functional testing was conducted across nine scenarios to verify the monitoring and control capabilities of the system. The results show that the ESP32 successfully connected to the WiFi network and Blynk Cloud with a connection success rate of 100%, confirming that the network configuration and Authentication Token were correctly configured. The system was able to execute lighting control commands with an average response time of 0.36 seconds, ranging from 0.1 to 0.8 seconds. In addition, the lamp status was accurately displayed through a virtual pin on the Blynk dashboard according to the actuator condition. The use of Wokwi enabled system development and testing without requiring physical hardware, thereby accelerating the validation process. The findings indicate that the integration of ESP32 and Blynk can serve as a simple and scalable prototype for IoT-based smart home development.